INNOVATION AND ADVANCED TECHNOLOGIES IN UKRAINE AND OTHER COUNTRIES - SYHYDA, Liubov; PALMOV, Volodymyr; LI, Yueyun (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the leading indicators of socio-economic development of individual countries, including the share of GDP of individual countries in the world GDP, the share of the country's population in the world population, GDP per capita, and expenditures on R&D. It was determined that a larger share of GDP per capita allows for an increase in gross domestic spending on R&D, % of GDP. Ukraine has the lowest gross domestic expenditure on R&D compared to the analyzed countries, only 0.29% of GDP. While for China, this indicator is equal to 2.433%, for Hungary – 1.642%, and for Germany – 3.129%.A comparison of the position of Ukraine according to the components of the Global Innovation Index, which corresponded to other countries at different stages of economic development, made it possible to obtain the following results. First, Ukraine needs to catch up in all components with developed countries. Second, Ukraine can compete on the components of the innovation index with some newly industrialized nations, such as Mexico and South Africa. Third, Ukraine dominates the least developed countries in the components of the Global Innovation Index.Also, we analyzed the opportunities for frontier technologies in Ukraine and other countries. According to this index, Ukraine ranks 58th among 166 countries surveyed. The five countries, including the United States of America, Sweden, Singapore, Switzerland, and the Netherlands, are leaders. China took 35th place. According to the components of this index, Ukraine already has a good position in terms of information and communication technologies and skills – however, R&D, industry, and finance remain weaknesses.So, during the study, "bottlenecks" were identified. Insufficient support for R&D and low costs restrain the innovative development of Ukraine.
Keywords: innovations; innovative activity; advanced technologies; R&D; costs